Quake - Akdeniz, Gülsüm Yağmur (Satura, 2024)
This text provides a concise recount of my experience during the 2023 Turkey earthquake. From the initial tremors to the aftermath, it chronicles the challenges faced and emotions felt. Through everyday moments and unexpected disruptions, this narrative offers a glimpse into the reality of living through a natural disaster. This is a firsthand account of a real experience endured during the 2023 earthquake in Turkey.